Cantāṉa Kuravar nāṉmaṇi mālai - Mīṉaṭcicuntarampiḷḷai, Ta. Ca (SAMP early 20th-century Indian books project ;, 1951)
Hymns, in praise of Cantāṉa Kuravar, a form of Śiva, Hindu deity; edited with commentary.